Translation and adaptation of the Bipolar Prodrome Symptom Scale-Retrospective: Patient Version to Brazilian portuguese Tradução e adaptação da Bipolar Prodrome Symptom Scale-Retrospective: Patient Version para português brasileiro - Pedro Mario Pan; Danilo Rocha de Jesus; Ary Gadelha; Rodrigo Affonseca Bressan; Christoph U. Correll; Rodrigo Barbachan Mansur; André Zugman; Cristiano Noto; Elson de Miranda Asevedo; Elisa Brietzke (Trends in Psychiatry and Psychotherapy, 2013)
BACKGROUND: Bipolar disorder (BD) is a chronic and often severe mental disease, associated with a significant burden in affected individuals. The characterization of a premorbid (prodromal) period and possible development of preventive interventions are recent advances in this field. Attempts to characterize high-risk stages in BD, identifying symptoms prior to the emergence of a first manic/hypomanic episode, have been limited by a lack of standardized criteria and instruments for assessment. The Bipolar Prodrome Symptom Scale-Retrospective (BPSS-R), developed by Correll and collaborators, retrospectively evaluates symptoms that occur prior to a first full mood episode in individuals with BD. OBJECTIVE: To describe the translation and adaptation process of the BPSS-R to Brazilian Portuguese. METHOD: Translation was conducted as follows: 1) translation of the scale from English to Brazilian Portuguese by authors who have Portuguese as their first language; 2) merging of the two versions by a committee of specialists; 3) back-translation to English by a translator who is an English native speaker; 4) correction of the new version in English by the author of the original scale; 5) finalization of the new version in Brazilian Portuguese. RESULTS: All the steps of the translation process were successfully accomplished, resulting in a final version of the instrument. CONCLUSIONS: The Brazilian Portuguese version of the BPSS-R is a potentially useful instrument to investigate prodromal period of BD in Brazil. INTRODUÇÃO: O transtorno bipolar (TB) é um transtorno mental crônico e muitas vezes grave, associado a um significativo prejuízo psicossocial nos indivíduos afetados. A caracterização de um período pré-mórbido (prodrômico) e o possível desenvolvimento de intervenções preventivas são avanços recentes na área. Tentativas de caracterizar estágios de alto risco para o TB, através da identificação de sintomas antes do aparecimento de um primeiro episódio maníaco/hipomaníaco, têm sido limitadas pela falta de critérios padronizados e instrumentos de avaliação. A Bipolar Prodrome Symptom Scale-Retrospective (BPSS-R), desenvolvida por Correll e colaboradores, avalia retrospectivamente os sintomas que ocorrem antes de um episódio sindrômico de humor em indivíduos com TB. OBJETIVO: Descrever o processo de tradução e adaptação da BPSS-R para português brasileiro. MÉTODO: A tradução foi conduzida como segue: 1) tradução da escala de inglês para português brasileiro por autores que têm o português como língua materna; 2) junção das duas versões por um comitê de especialistas; 3) retrotradução para inglês por um tradutor que tem inglês como língua materna; 4) correção da nova versão em inglês pelo autor do instrumento original; 5) finalização da nova versão em português brasileiro. RESULTADOS: Todos os passos do processo de tradução foram completados com sucesso, resultando em uma versão final do instrumento. CONCLUSÕES: A versão da BPSS-R em português brasileiro é um instrumento potencialmente útil para investigar o período prodrômico do TB no Brasil.